The Role of Public Relations in Organizational Culture to Build Management Loyalty: Case Study of the Faculty Student Representative Body, Faculty of Information Technology, Satya Wacana Christian University, Salatiga - Wijaya, Lina Sinatra; Fenetta, Christella (Communicare : Journal of Communication Studies, 2024)
The success and survival of management in an organization cannot be separated from the totality, productivity, and loyalty of management. So management is one of the most determining aspects in an organization. However, most organizations focus too much on communicating with external parties and achieving success that is visible from the outside but forgets to pay attention to the internal aspects of the organization. For this reason, in an organization the role of Public Relations (PR) is needed to build management loyalty. This research aims to determine the role of Public Relations in organizational culture to build management loyalty. Data collection was carried out using observation, interviews, and documentation. The research results show that four Public Relations roles are applied internally, namely expert prescriber, communication facilitator, problem-solving process facilitator, and communications technician. Evidence of management loyalty which is formed from the role of Public Relations implemented in the internal sphere can be seen from several management attitudes and actions which include obedience and conformity, responsibility, honesty, willingness to understand organizational difficulties, working more than required, creating pleasant atmosphere in the organization, and being open to change.